ELECTRIC CARS IN SLOVENIA - Srpčič, Gregor (Journal of Energy Technology, 2024)
This article deals with electric vehicles in Slovenia. The introduction of electric cars is necessary in order to achieve the objectives of the European Union’s strategy for reducing CO 2 emissions from road vehicles. In the first part of the article, the development of electric cars and their functioning is described. A key component of electric cars are batteries; therefore, various types of batteries, battery charging, and types of charging stations, which occur in Slovenia, are described in this article. An extensive network of charging stations is essential for the use of electric vehicles. A map of charging stations and the number of charging stations in Slovenia are presented. Currently, the most charging stations are located in central Slovenia; this is in the area around Ljubljana. In addition, to an extensive network of charging stations, the introduction of electric vehicles also requires financial incentives to buyers of electric vehicles. Slovenian environmental public funds or Eco Fund grants provide financial incentives to buyers of electric cars. In Slovenia, there are two types of financial incentives.